Organizational factors explaining the introduction of digital technology in the company: A qualitative analysis with managers of SMEs in Agadir city - M'barka BOUHOUILI (Moroccan Journal of Quantitative and Qualitative Research, 2021)
Today, digital technology is being introduced everywhere in companies, which increasingly look to improve their assets in order to best meet the needs of customers, better communicate with suppliers and achieve profitability on all levels. However, there are several factors that influence the implementation of digital technologies and impact their development, they are of various types: cultural, environmental, technological and organizational...